Displacement Characteristics of Stiffened Column-Beam End-Plate Joints: A Comparative Study - Rada, Dwi Cahya; Zulfakar, Muhamad (Sustainable, 2024)
This study investigates the mechanical behavior of extended end-plate moment connections in steel structures, with a focus on the variations in stiffener angle and position. Utilizing finite element analysis (FEA), three models featuring different stiffener configurations were assessed to evaluate their rotational capacity and displacement characteristics. The results indicate that adding a stiffener to the moment connection between the beam and the column at the bottom of the connection increases the rotational capacity by 32.60% when comparing the flush type of end plate to a model with a 45° single rib stiffener. Additionally, the implementation of double stiffeners significantly enhances the rotational capacity, improving performance by up to 59.85% compared to unstiffened configurations. Increasing the angles of the stiffeners further optimizes load distribution and structural integrity. These findings highlight the importance of stiffener design in moment connections, particularly regarding rotational capacity. Future research should explore the effects of bolt pretension and the use of varied bolt diameters for further optimization.